Μ⋆ masses: weak-lensing calibration of the Dark Energy Survey Year 1 redMaPPer clusters using stellar masses. Issue 4 (7th September 2020) - Pereira, M E S; Palmese, A; Varga, T N; McClintock, T; Soares-Santos, M; Burgad, J; Annis, J; Farahi, A; Lin, H; Choi, A; DeRose, J; Esteves, J; et al.
ABSTRACT: We present the weak-lensing mass calibration of the stellar-mass-based μ⋆ mass proxy for redMaPPer galaxy clusters in the Dark Energy Survey Year 1. For the first time, we are able to perform a calibration of μ⋆ at high redshifts, z > 0.33. In a blinded analysis, we use ∼6000 clusters split into 12 subsets spanning the ranges 0.1 ≤ z < 0.65 and μ⋆ up to 5.5 × 10^13 M_, and infer the average masses of these subsets through modelling of their stacked weak-lensing signal. In our model, we account for the following sources of systematic uncertainty: shear measurement and photometric redshift errors, miscentring, cluster-member contamination of the source sample, deviations from the Navarro–Frenk–White halo profile, halo triaxiality, and projection effects. We use the inferred masses to estimate the joint mass–μ⋆ – z scaling relation given by M_200c | μ _, z = M_0 (μ _/5.16× 10^12 M_)^F_μ _ ((1+z)/1.35)^G_z . We find M_0= (1.14 ± 0.07) × 10^14 M_ with F_μ _= 0.76 ± 0.06 and Gz = −1.14 ± 0.37. We discuss the use of μ⋆ as a complementary mass proxy to the well-studied richness λ for: (i) exploring the regimes of low z, λ < 20 and high λ, z ∼ 1; and (ii) testing systematics such as projection effects for applications in cluster cosmology.